Arguing from Experience: Travelees versus Travelers in Early Modern Exchanges. Issue 4 (14th August 2019) - Bracewell, Wendy
Abstract: How and why did early modern European 'travelees' dispute the accounts of their societies by foreign travel writers? A surprising number did so, challenging travelers' claims to authority while countering foreign characterizations of their societies as fundamentally different from those of the travelers. This article examines several such rebuttals, from the sixteenth to the eighteenth centuries, as new sources for the cultural history of travel as experience. The travelees' key criticism was that of the travelers' epistemological limitations. Both travelers and travelees agreed on the importance of eyewitness experience as the basis for knowledge; but travelees effectively argued that even accurate reports of travel experience could be unreliable as the basis for ethnographic knowledge, since foreign travelers lacked the cultural competence to interpret their experiences. In turn, the travelees discussed here put forward their own alternative views of their societies, based on insider knowledge, as more authoritative and reliable. These travelees legitimated their counter‐narratives according to the same standards and protocols as their opponents, arguing for the commensurability of nature, of European cultures and of experience. The reception of their rebuttals suggests, however, that their critics judged such travelee‐polemicists by different standards than they did travelers from their own cultural context.